Going underground: Resort to terrorism in mass mobilization dissident campaigns. (September 2018) - Belgioioso, Margherita
When and why do groups participating in mass dissent choose to initiate terrorist campaigns? I argue that groups involved in civil wars and mass civil resistance might face similar organizational pressures, which encourage the initiation of terrorism due to higher tactical effectiveness. Internal organizational pressure might depend on leaders' expectations of a decline in followers' commitment with protracted use of mass tactics. This is likely to motivate leaders to initiate terrorist campaigns to secure organizational survival. External organizational pressures might depend on increasing dissident campaigns' fragmentation. This intensifies competition making leaders more likely to initiate terrorism so as to establish themselves at the forefront of their movements. The findings provide empirical support consistent with my claims and indicate no significant difference between civil wars and mass civil resistance movements with regards to these effects. Contrary to the common idea that the use of conventional violence should entail a higher willingness to engage in illegal violence against non-combatants, this finding suggests that conflict dynamics affect the decision to initiate terrorism and that terrorist campaigns have a coherent strategic logic across different types of mass dissent.